Daptomycin-Induced Acute Eosinophilic Pneumonia: Late Onset and Quick Recovery - Mohamad Rachid; Khansa Ahmad; Meghan Saunders-Kurban; Aelia Fatima; Aditya Shah; Anas Nahhas (Case Reports in Pulmonology)
Background. Daptomycin is a cyclic lipopeptide antibiotic that provides great coverage for gram positive cocci. From the early years of daptomycin use, concerns were raised regarding the pulmonary side effects of daptomycin and potential development of acute eosinophilic pneumonia (AEP) secondary to daptomycin therapy. Discussion. AEP could be idiopathic or induced by drugs or toxins. It is a distinct entity from atopic diseases and autoimmune, parasitic, or fungal infections that can also cause pulmonary eosinophilia. Multiple medications are associated with acute eosinophilic pneumonia. Multiple cases of daptomycin-induced AEP have been reported in the literature. Diagnosis of AEP is based on clinical history, laboratory tests, and radiographic studies. Obtaining bronchoalveolar lavage or lung biopsy is needed to confirm the diagnosis. Timing of the drug use and clinical presentation is crucial in the diagnosis of drug-induced AEP. Discontinuation of the offending drug and systemic corticosteroids are the mainstay treatment with great outcomes and recovery. Conclusion. We present a case of AEP caused by daptomycin, with complete recovery after discontinuation of daptomycin and administration of steroids. The patient had AEP after almost 6 weeks of daptomycin therapy which has never been reported in literature and our patient achieved complete recovery with appropriate management.